Effectiveness of mHealth on self-care profile and blood pressure among patients with hypertension in Indonesia: A single-blind randomized controlled trial - Chatarina Setya Widyastuti; Lucia Kris Dinarti; Khudazi Aulawi; Lutfan Lazuardi (Belitung Nursing Journal)
Background: Self-management is essential for controlling blood pressure and requires consistent effort. Mobile health (mHealth) applications can support patients in independently managing hypertension and maintaining better control over their blood pressure.